Protective role of Limonium bonduelli extract against non-enzymatic peroxidation in brain and testes induced by iron in vitro. - Amel Amrani; Nassima Boubekri; Ouahiba Benaissa; Djamila Zama; Fadila Benayache; Samir Benayache (International Journal of Phytomedicine, 2017)
Infertility and Neurodegerative diseases have been linked to oxidative stress arising from peroxidation of membrane biomolecules and high levels of iron have been reported to play an important role. The present study sought to determine the antioxidant activity and protective ability of n-butanol extract of Limonium bonduelli on lipid peroxidation induced by FeSO4 in rat brain and testes homogenates in vitro. n-butanol extract of the aerial parts (leaves and flowers) was prepared, and the ability of the extract to inhibit FeSO4 induced lipid peroxidation in isolated rat brain and testes was determined using spectrophotometric method. The study revealed that the extract inhibited malondialdehyde (MDA) production in FeSO4 induced lipid peroxidation in the brain and testes in a dose-dependent manner and the highest percentage of the inhibition was 89.80% similar to vitamin C in the same concentration (100 µg/mL) in brain and 82.33% in testes (200 µg/mL). Limonium bonduelli extract demonstrated important anti-lipid peroxidative effect, which may be useful in preventing the progress of various oxidative stress related diseases. The higher inhibitory effect of the extract could be attributed to its phytochemical content.